The impact of liquidity on the capital structure of construction companies - Laili, Rizki Nurul; Dalimunthe, Sholatia (Ifma Publishing, 2022)
The purpose of this research is to examine the effect of liquidity on the capital structure of construction sub-sector companies listed on the Indonesia Stock Exchange. Data was collected using secondary data and library research. The population used in this study comprised all construction sub-sector companies listed on the Indonesia Stock Exchange from 2013–2020. In determining the sample, this research applied the purposive sampling method. This study used a sample of 10 construction sub-sector companies and managed and analyzed a total of 80 observational data using E-views software. The results indicate that liquidity has no significant effect on capital structure as measured by LTDAR. However, liquidity had a significant negative effect on capital structure as measured using DAR, DER, STDAR, LTDER, and STDER. The results support the pecking order theory, which states that liquidity and capital structure have a negative relationship.